Polarity of Human Parainfluenza Virus Type 3 Infection in Polarized Human Lung Epithelial A549 Cells: Role of Microfilament and Microtubule - Bose, Santanu (American Society for Microbiology, 2001)
Human parainfluenza virus type 3 (HPIV-3) is an airborne pathogen that infects the epithelial cells of the respiratory tract. In the present study we investigated the interaction of HPIV-3 with the type II alveolar human lung polarized epithelial A549 cells. Although HPIV-3 entry and budding were bidirectional from both the apical and the basolateral domains, HPIV-3 exhibited preferential entry and release from the apical pole. While disruption of the cellular actin microfilament and microtubule by cytochalasin D and nocodazole, respectively, had no effect on virus entry, disruption of the microtubule but not the microfilament inhibited HPIV-3 release.